The effect of preheating on the color stability of microhybrid composite resin after immersion in carbonated beverages and black tea: an experimental study - Nugroho, Raditya; Penga, Yohana Maria; Al Ghifari, Faiq Aqil; Wulandari, Erawati; Hidayati, Lusi (Universitas Padjadjaran, 2024)
Introduction: Composite resin is commonly used in restorative dentistry due to its pleasing aesthetics. However, this material tends to experience discoloration, a vital standard reflecting the restoration’s success. Studies show that preheating is effective in maintaining the color stability of other types of composite resin; nevertheless, the effect on microhybrid composite resin is not fully understood. This study aimed to analyze the effect of preheating on the color stability of microhybrid composite resins after immersion in carbonated beverages and black tea. Method: Twenty-four Z250 shade A2 composite resin discs, each with a diameter of 7 mm and a thickness of 2 mm, were divided into four groups (n=6). While groups I and II underwent a preheating process at 68°C before being soaked in carbonated drinks and black tea, groups III and IV were prepared at room temperature (25°C) without preheating and soaked in carbonated drinks and black tea. The discoloration of the samples was determined utilizing a UV-Vis spectrophotometer according to CIEL*a*b* color space. Data were analyzed using one-way ANOVA followed by the Least Significant Difference (LSD) test. Result: Preheating increased the color stability of composite resins. Preheated composite resins experienced significantly lower discoloration than composite resins at room temperature after soaking in carbonated drinks and black tea (p<0.05). Conclusion: preheating can minimize the color change of microhybrid composite resin after immersion in carbonated beverages and black tea.